Polar Mesospheric Clouds Formed From Space Shuttle Exhaust - Stevens, Michael H.; Gumbel, Jorg; Englert, Christoph R.; Grossmann, Klaus U.; Rapp, Markus; Hartogh, Paul (2003)
We observe a plume of water vapor in the Arctic above 85 km and a day after an August shuttle launch. Our satellite observations reveal that a discrete region of polar mesospheric clouds (PMCs) appears a week after that launch. We calculate that the water contained in the observed PMCs is consistent with the amount injected by the shuttle. This is evidence for a source of PMCs not previously considered. Published in Geophysical Research Letters, v30 n10 p53-1 through 4, 2003.